Worker participation from a comparative perspective: Lessons from South Africa - Conradie, Bradley Neil (Institute of Development and Labour Law, 2024)
The concept of worker participation in industry can be regarded as a new addition to South African labour law. The new Labour Relations Act provides for the establishment of workplace forums in an attempt to give workers a say in the running of the enterprises in which they work. As this concept is a new one in our labour law, in drafting the relevant provisions of the Act much emphasis was placed on the experiences in other jurisdictions in which worker participation systems have been in existence for quite some time. Any study of worker participation in general as well as in relation to South Africa will be incomplete if these experiences are not taken into condsideration. The European experience, in particular that of Germany was heavily drawn on by the drafters of the new Act and it will undoubtedly continue to be a valuable source of information on worker participation in the future. As far as the African experience is concerned research in this area is sorely lacking making it extremely difficult to properly ascertain the extent to which worker participation is taking place in Africa. The development of worker participation in terms of the Act could be severely limited if the trade union movement does not lend its support to the concept and accordingly refuse to trigger the establishment of workplace forums. At this early stage in the existence of the new Act it is not possible to determine with any accuracy whether workplace forums will be a suitable vehicle for worker participation in South Africa. What is certain, however, is that any attempt to understand worker participation in South Africa will be incomplete in the absence of an international perspective.